A Multicomponent Magnetic Proxy for Solar Activity - Harry P. Warren; Linton E. Floyd; Lisa A. Upton (Space Weather)
Abstract We present a new, multicomponent magnetic proxy for solar activity derived from full disk magnetograms that can be used in the specification and forecasting of the Sun’s radiative output. To compute this proxy we project Carrington maps, such as the synchronic Carrington maps computed with the Advective Flux Transport (AFT) surface flux transport model, to heliographic cartesian coordinates and determine the total unsigned flux as a function of absolute magnetic flux density. Performing this calculation for each day produces an array of time series, one for each flux density interval. Since many of these time series are strongly correlated, we use principal component analysis to reduce them to a smaller number of uncorrelated time series. We show that the first few principal components accurately reproduce widely used proxies for solar activity, such the the 10.7 cm radio flux and the Mg core‐to‐wing ratio. This suggests that these magnetic time series can be used as a proxy for irradiance variability for emission formed over a wide range of temperatures.